Two Potts Models on Cayley Tree of Arbitrary Order - Ganikhodjaev, Nasir; Nawi, Ashraf Mohamed; Rodzhan, Mohd Hirzie (Institute of Physics Publishing, 2012)
On a Cayley tree of arbitrary order k we consider two different Potts models with competing nearest-neighbour interactions J1 and next-nearest-neighbour interactions Jp and Jo, where coupling Jp corresponds to interaction of spins belonging to the same branch of the tree (prolonged) and coupling Jo corresponds to interaction of spins belonging to the same shell of the tree (one-level) and find for each model in addition to the expected paramagnetic, ferromagnetic and antiferromagnetic phases, an intermediate range of coupling values where the local magnetization has chaotic oscillatory glass-like behaviour. We also show that the ranges corresponding two models are different